Pro-inflammatory cytokine responses in human gingival epithelial cells after stimulation with cell wall extract of Aggregatibacter actinomycetemcomitans subtypes - Nuntiya Pahumunto (2018)
© 2017 Elsevier Ltd Varying cytokine responses of human gingival epithelial cells (HGECs) by Aggregatibacter actinomycetemcomitans subtypes have been found. Most studies have used reference strains, whereas a few has evaluated the cytokine expression in response to clinical subtypes of this bacterial species. This study aimed to examine whether there was any difference in cytokine responses of HGECs stimulated with cell wall extract (CWE) from A. actinomycetemcomitans subtypes included clinical strains from Thai adult periodontitis, various serotypes and non-serotypeable strains, strains from deep or shallow pockets, and reference serotype strains. Totally 50 clinical strains and 7 reference strains of A. actinomycetemcomitans were analyzed for the expression of IL-1β, IL-6, IL-8, and TNF-α mRNAs in HGECs by real time-PCR, and the IL-8 concentrations in cell-free supernatant measured using ELISA. An in vitro effect of released IL-8 on neutrophil migration was examined using transwell chambers. Result showed that among four cytokines studied, IL-8 mRNA was highly up-regulated by both clinical and reference strains. Serotype f revealed the highest expression compared to other serotypes. The JP2-like leukotoxin promoter gene and non-serotypeable (NS1 and NS2) demonstrated lower IL-8 responses compared to serotypeable strains, and IL-8 responses upon stimulation with clinical strains from deep pockets were also significantly lower than those isolated from shallow pockets (P < 0.01). Our findings suggest that the clinical isolates of A. actinomycetemcomitans associating with deep pockets, JP2-like leukotoxin promoter gene, NS1, and NS2 may interfere neutrophil function via minimal and immunosuppressing IL-8 responses, which may enhance their survival and virulence.